2015
DOI: 10.1590/s1677-5538.ibju.2014.0289
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Coverage of the Prostate, Normal Tissue Sparing, and Acute Toxicity with High-Dose-Rate Brachytherapy for Large Prostate Volumes

Abstract: PurposeTo evaluate dosimetric coverage of the prostate, normal tissue sparing, and acute toxicity with HDR brachytherapy for large prostate volumes.Materials and MethodsOne hundred and two prostate cancer patients with prostate volumes >50 mL (range: 5-29 mL) were treated with high-dose-rate (HDR) brachytherapy ± intensity modulated radiation therapy (IMRT) to 4,500 cGy in 25 daily fractions between 2009 and 2013. HDR brachytherapy monotherapy doses consisted of two 1,350-1,400 cGy fractions separated by 2-3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…This study provides a comprehensive analysis of patients’ pelvic radiation disease symptoms following EBRT plus HDR brachytherapy for prostate cancer. Consistent with previous studies, we found that bowel side-effects were infrequent [ 14 , 15 ]. Furthermore, we found that patients generally recovered from treatment over time with fewer bowel symptoms reported at 12 months.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study provides a comprehensive analysis of patients’ pelvic radiation disease symptoms following EBRT plus HDR brachytherapy for prostate cancer. Consistent with previous studies, we found that bowel side-effects were infrequent [ 14 , 15 ]. Furthermore, we found that patients generally recovered from treatment over time with fewer bowel symptoms reported at 12 months.…”
Section: Discussionsupporting
confidence: 92%
“…Using the EORTC proctitis module offered the advantage of capturing the range of pelvic symptoms patients experienced following EBRT and HDR brachytherapy. Other studies using clinician-reported instruments did not describe the range of symptoms we explored or the incidence of symptoms aside from rectal bleeding [ 14 , 15 ]. The most commonly experienced symptoms included feeling of bloating and passing excessive wind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate gland size (commonly defined as .60 cm 3 ) remains a relative contraindication to brachytherapy according to the ABS. While several studies have called this recommendation into question [34,[42][43][44][45], achieving an adequate dose distribution for larger prostate glands remains a challenge, particularly for less experienced brachytherapists. Furthermore, patients with larger prostate glands are more likely to be symptomatic often making them unsuitable candidates for PB.…”
Section: Discussionmentioning
confidence: 99%
“…To create an equal comparison between SBPT and SBXT plans, target coverage and dose heterogeneity of the CTV (prostate) was evaluated and compared. Target coverage and dose heterogeneity goals shown in Table 1 were designed to reflect HDR-B dosimetry reported in the literature [ 32 34 ]. As per ABS guidelines, the CTV (prostate) was required to have 100% of the volume receiving 90% or greater of the prescription dose (V100 ≥ 90%) [ 12 ].…”
Section: Methodsmentioning
confidence: 99%